Expert perspectives on polmacoxib monotherapy in the management of osteoarthritis in Indian settings - S., Manjula; Kumar M., Krishna (International Journal of Research in Orthopaedics, 2024)
Background: Although there were several clinical studies available, there was a dearth of studies among clinicians in actual practice. So, the present survey-based study aimed to gather expert perspectives on the clinical use of polmacoxib monotherapy for the management of osteoarthritis (OA) in routine Indian settings. Methods: This cross-sectional study employed a 19-item questionnaire to gather expert opinions on managing OA and covered topics such as prescription practices, clinical observations, preferences and experiences with polmacoxib for routine OA management. Descriptive statistics were used to analyze the gathered data. Results: The study involved 239 participants, with 45% of respondents noting that 31-40% of OA patients are women. According to 65% of the participants, etoricoxib emerged as the most preferred nonsteroidal anti-inflammatory drug (NSAID) in clinical practice. Moreover, 87% of experts recognized the dual cyclooxygenase-2 (COX-2) and carbonic anhydrase (CA) binding properties of polmacoxib as potentially offering superior safety profiles in cardiovascular (CV), renal aspects and Gastrointestinal (GI) tolerability. Around 35% of respondents observed improvements in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), pain reduction, stiffness alleviation and enhanced physical function with polmacoxib. Conclusions: The study highlighted a significant preference among Indian clinicians for polmacoxib in managing OA, primarily due to its dual COX-2 and CA binding properties that potentially offer better safety profiles in terms of cardiovascular, renal and GI tolerability. Additionally, the observed improvements in pain, stiffness and physical function with polmacoxib underscore its effectiveness as a monotherapy in routine OA management.